Identification of a New Pathogenicity Island Within the Large pAH187_270 Plasmid Involved in Bacillus cereus Virulence - Dervyn, Rozenn; Kavanaugh, Devon W.; Cormontagne, Delphine; Glasset, Benjamin; Ramarao, Nalini (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives Bacillus cereus is responsible for food poisoning and rare but severe clinical infections. The pathogenicity of B. cereus strains varies from harmless to lethal strains. The objective of this study was to characterize three B. cereus isolates isolated from the same patient and identify their virulence potentials. Methods Three isolates of B. cereus were isolated from various blood samples from a patient who developed sepsis following a central venous catheter infection. The three isolates were compared by WGS, genotyping and SNP analysis. Furthermore, the isolates were compared by phenotypical analysis including bacterial growth, morphology, germination efficacy, toxin production, antibiotic susceptibility and virulence in an insect model of infection. Results According to WGS and genotyping, the 3 isolates were shown to be identical strains. However, the last recovered strain had lost the mega pAH187_270 plasmid. This last strain showed different phenotypes compared to the first isolated strain, such as germination delay, different antibiotic susceptibility and a decreased virulence capacity towards insects. A 50- kbp region of pAH187_270 plasmid was involved in the virulence potential and could thus be defined as a new pathogenicity island of B. cereus. Conclusions These new findings help in the understanding of B. cereus pathogenic potential and complexity and provide further hints into the role of large plasmids in the virulence of B. cereus strains. This may provide tools for a better assessment of the risks associated with B. cereus hospital contamination to improve hygiene procedure and patient health.